2021
DOI: 10.1039/d1tc00880c
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency Cu2ZnSnS4 solar cells over FTO substrates and their CZTS/CdS interface passivation via thermal evaporation of Al2O3

Abstract: Fabrication on SLG/FTO transparent substrates gives an important advance to fabrication of tandem solar cells. In addition, a possible passivation using Al2O3 which can be deposited with cheap systems can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…The chalcogenization thermal profiles and conditions have been optimized for the growth of kesterite thin film for photovoltaic applications, as previously described in refs. [46][47][48][49]. An illustration of the thermal profiles is presented in the Supporting Information.…”
Section: Thin Film Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The chalcogenization thermal profiles and conditions have been optimized for the growth of kesterite thin film for photovoltaic applications, as previously described in refs. [46][47][48][49]. An illustration of the thermal profiles is presented in the Supporting Information.…”
Section: Thin Film Preparationmentioning
confidence: 99%
“…Surprisingly, it emerges a substantial scarcity of TE investigation for the thin film configuration of these materials, [67,68] despite the vast knowledge acquired in their fabrication and PV characterization. [46,[69][70][71] Following literature guidelines on bulk counterparts, [60,66] a 12.5% Cu doped (in place of Zn) composition is selected for the thin films fabricated in this work.…”
Section: Structural Optical and Compositional Characterization Of The...mentioning
confidence: 99%
“…[10,[13][14][15] In CZTS solar cells, various wide-bandgap thin insulating metal oxide films such as Al 2 O 3 and SnO 2 are incorporated at heterointerface to passivate the CZTS surface defects and electrically active interfacial trap states to mitigate the back interface recombination. [12,16,17] The influence of insulating material Al 2 O 3 has been investigated widely in CZTS solar cells at the front interfacial contact as well as at the back contact of CZTS DOI: 10.1002/pssa.202200001…”
Section: Introductionmentioning
confidence: 99%
“…absorber. [16,18,19] Al 2 O 3 effectively passivates the surface and interface states, improves the collection efficiency, and hence results in enhanced device performance. Sun et al revealed that the implemented SnO 2 film behaves as an electron-selective contact for CZTS and blocks the holes away from the buffer layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation